Activation of the Wnt Pathway by Mycobacterium tuberculosis: A Wnt–Wnt Situation - Villaseñor, Tomás; Madrid-Paulino, Edgardo; Maldonado-Bravo, Rafael; Urbán-Aragón, Antonio; Pérez-Martínez, Leonor; Pedraza-Alva, Gustavo (Frontiers in Immunology, 2017)
Mycobacterium tuberculosis (M. tuberculosis), an intracellular pathogenic Gram-positive bacterium, is the cause of Tuberculosis, a major worldwide human infectious disease. The innate immune system is the first host defense against M. tuberculosis. The recognition of this pathogen is mediated by several classes of pattern recognition receptors (PRRs) expressed on the host innate immune cells, including Toll-like receptors, Nod-like receptors and C-type lectin receptors like Dectin-1, the Mannose receptor, and DC-SIGN. M. tuberculosis interaction with any of these receptors activates multiple signaling pathways among which the PKC, the MAPK and the NFκB pathways have been widely studied. These pathways have been implicated in macrophage invasion, M. tuberculosis survival and impaired immune response, thus promoting a successful infection and disease. Interestingly, the Wnt signaling pathway, classically regarded as a pathway involved in the control of cell proliferation, migration and differentiation in embryonic development, has recently been involved in immunoregulatory mechanisms in infectious and inflammatory diseases, such as tuberculosis, sepsis, psoriasis, rheumatoid arthritis and atherosclerosis. In this review we present the current knowledge supporting a role for the Wnt signaling pathway during macrophage infection by M. tuberculosis and the regulation of the immune response against M. tuberculosis. Understanding the cross-talk between different signaling pathways activated by M. tuberculosis, will impact on the search for new therapeutic targets to fuel the rational design of drugs aimed to restore the immunological response against M. tuberculosis.